Helicobacter pylori second‐line rescue therapy with levofloxacin‐ and bismuth‐containing quadruple therapy, after failure of standard triple or non‐bismuth quadruple treatments. Issue 8 (23rd February 2015) - Gisbert, J. P.; Romano, M.; Gravina, A. G.; Solís‐Muñoz, P.; Bermejo, F.; Molina‐Infante, J.; Castro‐Fernández, M.; Ortuño, J.; Lucendo, A. J.; Herranz, M.; Modolell, I.; del Castillo, F.; et al.
Summary: Background: The most commonly used second‐line Helicobacter pylori eradication regimens are bismuth‐containing quadruple therapy and levofloxacin‐containing triple therapy, both offering suboptimal results. Combining bismuth and levofloxacin may enhance the efficacy of rescue eradication regimens. Aims: To evaluate the efficacy and tolerability of a second‐line quadruple regimen containing levofloxacin and bismuth in patients whose previous H. pylori eradication treatment failed. Methods: This was a prospective multicenter study including patients in whom a standard triple therapy (PPI–clarithromycin–amoxicillin) or a non‐bismuth quadruple therapy (PPI–clarithromycin–amoxicillin–metronidazole, either sequential or concomitant) had failed. Esomeprazole (40 mg b.d.), amoxicillin (1 g b.d.), levofloxacin (500 mg o.d.) and bismuth (240 mg b.d.) was prescribed for 14 days. Eradication was confirmed by 13 C‐urea breath test. Compliance was determined through questioning and recovery of empty medication envelopes. Incidence of adverse effects was evaluated by questionnaires. Results: 200 patients were included consecutively (mean age 47 years, 67% women, 13% ulcer). Previous failed therapy included: standard clarithromycin triple therapy (131 patients), sequential (32) and concomitant (37). A total of 96% took all medications correctly. Per‐protocol and intention‐to‐treat eradication rates were 91.1% (95%CI = 87–95%) and 90% (95%CI = 86–94%). Cure rates were similar regardless of previous (failed) treatment or country of origin. Adverse effects were reported in 46% of patients, most commonly nausea (17%) and diarrhoea (16%); 3% were intense but none was serious. Conclusions: Fourteen‐day bismuth‐ and levofloxacin‐containing quadruple therapy is an effective (≥90% cure rate), simple and safe second‐line strategy in patients whose previous standard triple or non‐bismuth quadruple (sequential or concomitant) therapies have failed.